Field and Laboratory Methods for Grassland and Animal Production Research 2000
DOI: 10.1079/9780851993515.0029
|View full text |Cite
|
Sign up to set email alerts
|

Modelling pasture and animal production.

Abstract: The prediction of pasture and animal production using a series of mathematical equations based on various biophysical inputs which influence or control production is outlined. These equations are arranged in a computer program and know as a model. The terminology and concepts used in models are discussed. Types of models and the user groups to which they apply are described. Getting started as a model user and as a model builder are outlined. Full details are given of a basic soil-plant-animal model with pastu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 0 publications
1
56
0
2
Order By: Relevance
“…This is described in Equation [20], which is similar to the results reported by Rickert et al (2000) and shown in Figure 2b. …”
Section: Grassland Transpirationsupporting
confidence: 81%
See 4 more Smart Citations
“…This is described in Equation [20], which is similar to the results reported by Rickert et al (2000) and shown in Figure 2b. …”
Section: Grassland Transpirationsupporting
confidence: 81%
“…When the soil water content is higher than the permanent wilting point, evaporation occurs at a rate equal to potential evaporation (Ep, ). This variable depends on the reference evapotranspiration (Eo, mm d -1 ) and effective soil cover (COB ef ) expressed as a fraction between 0 and 1 (Rickert et al, 2000). When soil water is lower than the permanent wilting point, evaporation is reduced by the relative water content in the layer (WDIv), which is referred to as residual water content estimated at one third of the permanent wilting point (Campbell, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations